Pembinaan Kegiatan Budaya dan Lingkungan Berkelanjutan di Desa Bengkel, Tabanan - Sinarsih, Ni Ketut; Gani, Kadek; Antari, Ni Kadek Devi; Praditya, I Putu Yodia; Sutini, Ni Luh; Putra, I Ketut Aldi Darma; Sugiarti, Ni Kadek Mira; Ananda, I Kadek Yoga Prema; Nugraha, I Bagus Okky Surya; Candradewi, Ni Putu Diah; Rinaldy, Putu Denny Alvaro Bill; Wijayanti, Ni Kadek Widia; Putra, Putu Gede Wirananda Manggala,; Putra, Kadek Andi; Dewi, Komang Ayu Nanda Risna; Premayani, Ni Wayan; Sinta, Ni Ketut (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
Bengkel Village is one of the villages in Tabanan Regency, Bali Province, where 80% of the population are farmers with a rice field area of 225 Ha out of a total area of 291 Ha. This village has the largest subak land in Kediri District, so Bengkel Village is special because of the natural potential. The high potential possessed by Bengkel Village can be developed and preserved through training of several groups who have an important role in implementing and passing on the existing potential. The challenges faced are the vulnerability to cultural erosion due to technological advances, rapid population growth, changes in lifestyle, and increased production of consumer goods which results in drastic changes in the volume of waste produced. The methods used in this activity include activities related to education such as socialization and practice of sorting waste for elementary school children as well as out-of-class education, namely providing Balinese dance practice activities in banjar halls, training in the form of religious and cultural training in the form of mejejaitan and making klakat, as well as activities The direct approach is in the form of planting tree seedlings, following rivers, taking an active part in sorting waste and distributing compost at TPS3R, the Waste Bank, as well as providing rubbish bins at Balai Banjar. This service activity provides an increase in participants' abilities in both waste management and culture.